CORPORATE GOVERNANCE, INFORMATION ASYMMETRY, AND EARNINGS MANAGEMENT - Siregar, Sylvia Veronica; Bachtiar, Yanivi S. (UI Scholars Hub, 2005)
The purpose of this study is to investigate the relationship between corporate governance, information asymmetry, and earnings management. Prior research indicates that information asymmetry negatively correlated with earnings management (Richardson, 2001). As predicted, this study also found negative correlation between bid-ask spread, as a proxy of information asymmetry, and discretionary accruals, as a proxy of earnings management. In addition, we also test whether corporate governance mechanisms will impact the level of discretionary accruals and eventually affect firm value. We use several variables as proxies of corporate governance mechanisms such as institutional ownership, audit quality, independent board, and existence of audit committee. We found that audit committee has significant negative relation with discretionary accruals. This indicates that audit committee existence is effectively constraining the level of earnings management. This study also has that proportion of independent board and existence of audit committee increase the positive relationship between discretionary accruals and stock return. These indicates that earnings management conducted by firms having higher proportion of independent board and firms having audit committee will be valued higher by the market.